Sustainable Learning Development Utilizing Extended Reality (XR) Technology for the Indonesian Education Sector: An Exploratory Research Methodology - Wecka Imam YUDHISTYRA; Chalita SRINUAN (Communications of International Proceedings, 2022)
The purpose of this paper is to better understand the Indonesian higher education sector’s evolution and support using advanced information technology. This paper uses an exploratory research methodology approach. After mapping Indonesia's current situation and condition, a new level of extended reality (XR) technologies is proposed as a simple idea to transform the education system. Three rationales are generated to strengthen the idea of XR technologies used in supporting educational facilities and learning environments to improve the quality of education. First, the idea of independent learning (Merdeka Belajar), where students and institutions are self-standing, self-reliant, and have freedom of self-determination, is proposed (Merdeka Belajar Kampus Merdeka - MBKM). Second, due to the generous allocation of 20% of Indonesia’s state funds to education since 2009 with minimal success in raising student scores, it is proposed that funds should be allocated to new digital technologies such as XR and online learning. Finally, workflow transformation of the education system and learning environment with emerging XR technologies should be developed and implemented.
Keywords: Extended Reality (XR); Digital Education; Indonesia; Merdeka Belajar Kampus Merdeka (MBKM).